The determinants of foreign direct investment in Malaysia - Yii, Su Yi (Universiti Malaysia Sarawak, (UNIMAS), 2022)
In this study, the general objective is to identify the determinants of foreign direct investment in Malaysia from 1991 to 2020. FDI is considered as a growth engine since it provides desperately needed capital for investment, boosts host country competitiveness, and helps local businesses become more productive by using more effective technologies or investing in people and physical capital. Few tests are used in this study to determine whether short-run causality and long-run relationship exist between the four independent variables and foreign direct investment in Malaysia. The Augmented Dickey-Fuller (ADF) test and Phillips-Perron (PP) test showed that all the variables were stationary in the first difference. While the result from Johansen-Juselius Cointegration test showed that the variables have a long-term relationship since they share a cointegrating vector. For Granger Causality test, it showed that the inflation rate has a unidirectional causality with foreign direct investment. Then, from the result of Error Correction Term, it can conclude that there is a long-run relationship between FDI, OPN, EXCH, INF, and GDPG. Besides, the test of Variance Decomposition indicated that trade openness is the most exogenous variable and followed by foreign direct investment, exchange rate, inflation, and last but not least gross domestic product growth is the most endogenous variable. Furthermore, the result of Impulse Response Function showed that trade openness and exchange rate are negatively responding to the foreign direct investment in the long run while the inflation and gross domestic product growth are positively responding to the foreign direct investment in the long run. Thus, the government of Malaysia should take seriously any factors that can affect the foreign direct investment in our country to affect the economic growth.